Proceedings of the 38th International Conference on Software Engineering 2016
DOI: 10.1145/2884781.2884871
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of staying together while moving fast

Abstract: We report on the results of an empirical study conducted with 35 experienced software developers from 22 high-tech companies, including Google, Facebook, Microsoft, Intel, and others. The goal of the study was to elicit challenges that these developers face, potential solutions that they envision to these challenges, and research initiatives that they think would deliver useful results.Challenges identified by the majority of the study participants relate to the collaborative nature of the work: the availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 57 publications
2
20
0
1
Order By: Relevance
“…The number of professional developers included in this study is larger or similar to those considered in many prior work, e.g., [25,28,60]. Admittedly, it is possible that results differ for other groups of developers.…”
Section: Threats To Validitymentioning
confidence: 97%
“…The number of professional developers included in this study is larger or similar to those considered in many prior work, e.g., [25,28,60]. Admittedly, it is possible that results differ for other groups of developers.…”
Section: Threats To Validitymentioning
confidence: 97%
“…What is, hence, required are more studies that provide empirical evidence on industrial practice in variability management [Berger et al 2013] and end-user challenges. Here, an industrial context could open up various new commercial perspectives, such as the pressure to get the next product to the market; problems to find the right expert in a large organization; and the challenge of communicating and collaborating within multidisciplinary teams [Rubin and Rinard 2016]. On a "meta" level, when considering the research approaches adopted in the surveyed studies, we observed a wide variation in quality, for example, in terms of: having an explicit research methodology; having clear research questions and evaluation criteria; supporting the replicability of the work; providing a comparison against existing work; and discussing limitations and threats to validity.…”
Section: Discussionmentioning
confidence: 99%
“…Although software quality has always been a common topic in software engineering [5,35], most of the studies have focused on pre-release data, primarily due to the developers' concern about finding the appropriate balance between the amount of testing required and the quality of software (e.g. [62,12]). There have been a number of works on predicting and improving the software quality as well (e.g.…”
Section: Related Workmentioning
confidence: 99%